Government Ethics in the Age of Trump - Raviv, Adam (2021)
Americans’ trust in government officials has never been lower. Despite the intense public focus on ethics in government in recent years, legal scholarship on the subject has been sparse. This Article fills the gap by examining the ethics regime of the federal executive branch in depth, with a discussion of both the applicable ethics standards and the agencies and offices that are charged with ensuring that government officials comply with those standards. The Article describes how the current system heavily emphasizes prevention, education, and highly detailed disclosures while it rarely enforces the law against wrongdoers. A federal official in the United States is literally more likely to be struck by lightning than to be charged with violating a government ethics law. The Article then considers the federal government’s ethics regime through the lens of criminal deterrence theory and concludes that the current system is an example of what not to do if the goal is to discourage violations. To address this deficiency, the Article proposes a number of reforms to the current system to improve the deterrent effect of federal ethics standards, including a radical reimagining of the authority of government ethics officials